The Existence of First Indigenous Scouting Javaansche Padvinders Organisatie in Mangkunegaran - Renny Pujiartati (Yupa: Historical Studies Journal, 2019)
Scouting progress occurs when the national movement of Indonesia is progressive. Scouting is used as a forum to improve the noble character, skills, personality, and sense of nationality among Indonesian youth. Besides, scouting is a medium to strengthen a national awareness of Indonesian youth. The first indigenous scouting was Javaansche Padvinders Organisatie or abbreviated as JPO. This organization was founded by Mangkunegoro VII. The establishment of the JPO was followed by the establishment of other indigenous scouting organizations. This study aims to determine the background, development, and role of the first indigenous scouting of Javaansche Padvinders Organisatie (JPO) in Mangkunegaran.